Three-Dimensional Lithium Anode with an In Situ Generated Li2O-Rich Solid Electrolyte Interface for High-Rate and Long-Storage Lithium Battery - Ping Li; Xuan Liu; Yingke Zhou; Xiangyu Cheng; Luozhi Mo; Xiaohui Tian; Zhongzhi Yuan (Energies)
The limited rate performance of Li||CFx batteries hinders their wide application, owing to the low conductivity of CFx cathode material and the undesirable solid electrolyte interface (SEI) layer formed on the Li anode surface. Herein, a strategy for constructing a three-dimensional lithium anode (3D-Li anode) with high specific surface area and an in situ formed favorable SEI layer is proposed to enhance the interfacial stability and uniformity of ion transport and realize a Li||CFx battery with remarkable comprehensive performance. A 3D-Li anode (Li@CuO-Cu foam) is successfully constructed by molten Li infusion of a thermal oxidation processed copper foam. The lithiophilicity of the Cu foam framework is optimized by the formed CuO. The Li@CuO-Cu foam||CFx battery exhibits a high discharge specific capacity (1149.6 mAh g−1 at 0.1 C) along with a high discharge plateau voltage (2.65 V). At a high rate of 10 C, the 3D-Li anode-based batteries still demonstrate a discharge specific capacity of 463 mAh g−1, which is about 2.5 times that of the conventional Li||CFx, and exhibit excellent storage performance (620.3 mAh g−1 after storage at 55 °C for 90 days) and a low monthly self-discharge rate (1.28%). This work demonstrates a promising strategy to construct a three-dimensional lithium metal anode and significantly improve the rate and storage performance of Li||CFx batteries.